Impact of Demonetisation on Bank Stock - P, Triveni; Kumari, Anupama (Ushus Journal of Business Management, 2018)
This paper empirically examines the impact of demonetisation on Indian bank stock. On 8th November 2016, the Indian Prime Minister, Narendra Modi declared demonetisation in an unscheduled live broadcast. Currency notes of Rs 500 and Rs 1000 were demonetised from the midnight of 8th November 2016. This was issued to curb black money and corruption. During demonetisation, the index values of the stock market SENSEX, NIFTY and BANKEX went down. This research mainly focusses on how demonetisation affected the stock price of the top Indian banks. With the help of CAAR, change in return and change in volatility, the effect of demonetisation on the stock market was calculated. Furthermore, an understanding of the impact of demonetisation on bank stocks was attempted. The evaluation helped in concluding that there has been no impact on the bank stocks post demonetisation.